USE OF CHELATORS TO RESTORE THE FLOW RATE OF WATER WELLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The quality of groundwater, the service life and the operating mode of wells are the reason for the precipitation of salts and filter corrosion products in the pores of the near-filter zone and on the surface of the filters. The process of precipitation of salts and corrosion products of metal elements of wells is called colmatation. Mechanical, chemical and biological clogging leads to a decrease in the flow rate of wells. It is necessary to study the chemically complex and mineralogical multicomponent colmatant, which is the main cause of colmatation. For removing multicomponent bridging agent, it is necessary to investigate the possibility of using various reagents and methods. This article presents the results of a study on the selection of effective reagents for dissolving and removing clogging deposits from wells.